All-Fiber Dual-Parameter Sensor Based on Cascaded Long Period Fiber Grating Pair Fabricated by Femtosecond Laser and CO2 Laser. Issue 2 (4th March 2018) - Zhang, Wen; Hao, Jiaqi; Lou, Xiaoping; Dong, Mingli; Zhu, Lianqing
ABSTRACT: An all-fiber dual-parameter sensor based on cascaded long period grating pair fabricated by femtosecond laser and CO2 laser has been proposed and realized both theoretically and experimentally. The resonant wavelengths of LPFGs are 1557.80 nm and 1590.88 nm. In the strain range of 0–400 με, strain sensitivities are −7.2 pm/με for C-LPFG and −1.6 pm/με for F-LPFG. In the temperature range of 30–70°C, temperature sensitivities are −41.1 pm/°C for C-LPFG and −21.2 pm/°C for F-LPFG. By analyzing the resonant wavelength characterization, the proposed sensor can be efficiently used for dual-parameters measurement with promising application prospect and great research reference value.